Diagnóstico de dermatofitosis, mediante examen directo y cultivo ( Sabouraud), en caminos que llegan al hospital docente veterinario César Augusto Guerrero de la Universidad Nacional de Loja. - Benítez Contento, Digar Jonathan (2018)
Superficial mycoses are infections caused by dermatophytes, parasitic fungi of keratin that infect three anamorphic genera: Trichophyton spp., Microsporum spp. And Epidermophyton spp., They affect the skin and attachments, manifest by pillar affection, nail thickening, or plaques with erythema. And desquamation with active edges causing discomfort in the canines that suffer from them. In accordance with the above, the research was proposed, with objectives of determining the prevalence of dermatophytes by direct examination and culture (saboraud), identifying the prevalence according to age, origin, race and affected area of the body. For the identification of fungal species samples were taken of the lesion of skin, hair and scales with scalpel; a part of the sample was analyzed with 10% KOH with microscopic observation and the other part was cultivated on Sabouraud agar media and incubated for 8 to 10 days at 27 ° C. The identification of the isolated strains was made by the microscopic characteristics and macroscopic of the colonies. It was determined that a total of 63 canine samples with clinical signs of dermatophytosis, 47.61% were positive for fungi while 52.38% were negative, the agent that did more frequently was Trichophyton spp with 96.66% of the patients, followed by a 3.33% in which Epidermophyton spp. The predisposing factors that favored the acquisition and development of this type of fungal infections in this population were the source of food and the place of housing in deplorable conditions among other factors. Key words: Superficial mycoses, dermatomycoses, dermatophytes.